Obesity in urban Indonesia: evidence from the 2007 and 2018 Basic Health Research - Ferdina, Ayunina Rizky; Arfines, Prisca Petty; Aryastami, Ni Ketut (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND The prevalence of obesity in urbanizing Indonesia is rising, where the double burden of malnutrition poses a significant challenge. This study aimed to examine the prevalence and increment of obesity-related noncommunicable diseases (NCDs) of diabetes and hypertension. METHODS Secondary data from the latest 2018 Basic Health Research (RISKESDAS) were used to analyze the obesity rate and its associations with lifestyle, sociodemographics, and certain comorbidities among urban Indonesians. This study included non-pregnant adults aged ≥18 years who lived in the urban area and whose blood pressure and glucose levels were measured in the survey. Results were compared to a similar study using data from 2007. RESULTS The proportion of obesity among Indonesia’s urban population was more than doubled from 23.0% in 2007 to 50.1% in 2018 for obesity and 28.0% to 57.2% for central obesity. Additionally, females, individuals with higher socioeconomic status, and higher education levels exhibited a higher obesity prevalence. CONCLUSIONS Urban Indonesia has witnessed a dramatic rise in obesity prevalence. Our findings highlighted the urgent need for policymakers to consider the escalating prevalence of NCDs associated with obesity. Strengthening and concretizing health promotion and prevention policies at the community level are crucial to combat this alarming public health challenge.